Functional Evidence for the Critical Amino-Terminal Conserved Domain and Key Amino Acids of Arabidopsis 4-HYDROXY-3-METHYLBUT-2-ENYL DIPHOSPHATE REDUCTASE . Issue 1 (18th July 2014) - Hsieh, Wei-Yu; Sung, Tzu-Ying; Wang, Hsin-Tzu; Hsieh, Ming-Hsiun
Abstract : Key residues near the N-terminus and around the central active site are critical for the function of Arabidopsis 4-hydroxy-3-methylbut-2-enyl diphosphate reductase . Abstract: The plant 4-HYDROXY-3-METHYLBUT-2-ENYL DIPHOSPHATE REDUCTASE (HDR) catalyzes the last step of the methylerythritol phosphate pathway to synthesize isopentenyl diphosphate and its allyl isomer dimethylallyl diphosphate, which are common precursors for the synthesis of plastid isoprenoids. The Arabidopsis ( Arabidopsis thaliana ) genomic HDR transgene-induced gene-silencing lines are albino, variegated, or pale green, confirming that HDR is essential for plants. We used Escherichia coli isoprenoid synthesis H (Protein Data Bank code 3F7T) as a template for homology modeling to identify key amino acids of Arabidopsis HDR. The predicted model reveals that cysteine (Cys)-122, Cys-213, and Cys-350 are involved in iron-sulfur cluster formation and that histidine (His)-152, His-241, glutamate (Glu)-242, Glu-243, threonine (Thr)-244, Thr-312, serine-379, and asparagine-381 are related to substrate binding or catalysis. Glu-242 and Thr-244 are conserved only in cyanobacteria, green algae, and land plants, whereas the other key amino acids are absolutely conserved from bacteria to plants. We used site-directed mutagenesis and complementation assay to confirm that these amino acids, except His-152 and His-241, were critical for Arabidopsis HDR function. Furthermore, the Arabidopsis HDR contains an extra amino-terminal domain following the transit peptide that is highly conserved from cyanobacteria, and green algae to land plants but not existing in the other bacteria. We demonstrated that the amino-terminal conserved domain was essential for Arabidopsis and cyanobacterial HDR function. Further analysis of conserved amino acids in the amino-terminal conserved domain revealed that the tyrosine-72 residue was critical for Arabidopsis HDR. These results suggest that the structure and reaction mechanism of HDR evolution have become specific for oxygen-evolving photosynthesis organisms and that HDR probably evolved independently in cyanobacteria versus other prokaryotes.